Analisis Desain Interior Perpustakaan dalam Mendukung Kenyamanan Pemustaka di Perpustakaan STIKES Suaka Insan Banjarmasin - Ana Rizka Mashud; Rusdiana; Ainol Mardiah; Nor Sa’adah (Al-Ma mun Jurnal Kajian Kepustakawanan dan Informasi, 2026)
The library, as a pillar of an institution's existence, plays an important role and no longer functions merely as a place for storing and borrowing books. It has evolved into a public space that supports learning activities, research, and social interaction. In this context, the aspect of comfort becomes a crucial factor to consider. A descriptive qualitative research approach was conducted to analyze the interior design of the library in supporting user comfort at the STIKES Suaka Insan Library in Banjarmasin. Data collection techniques included interviews, observations, and documentation. Data analysis was carried out in three steps: data reduction, data presentation in narrative form, and finally, drawing conclusions. The research findings show that the interior design of the STIKES Suaka Insan Library in Banjarmasin was carefully planned and designed with user comfort and needs in mind. A minimalist aesthetic design is reflected in the bright wall colors and ceiling, symbolizing tolerance, as well as in the service layout, lighting, and temperature—all aspects aimed at creating a pleasant environment that supports the learning process. Keywords: library interior design; minimalist aesthetics; user comfort